Leveraging Three Lessons Learned From Teaching an HRD Undergraduate Diversity and Inclusion Course: An Autoethnography of One Professor's Perceptions. (May 2017) - Collins, Joshua C.
The Problem: As a field, human resource development (HRD) is still in the early stages of figuring out the best ways to make the fundamental theories and practices of our discipline more accessible and useful to traditionally aged undergraduate students. Concurrently, the nature of jobs and careers are changing, and on a grand scale, bachelor's degrees tend to no longer yield the same opportunities they used to. There is a growing expectation that new college graduates will be, among other things, savvy with/toward diversity and social justice, yet we know little about how HRD undergraduate programs function to prepare students to meet this demand. The Solution: The purpose of this autoethnographic exploration was to detail and reflect upon one professor's perceptions of the experience of teaching a diversity and inclusion course to HRD undergraduates at a predominantly White institution (PWI). Findings revealed three lessons learned: (a) valuing student expertise; (b) recognizing and counteracting implicit bias, both in the self and students; and (c) challenging student assumptions. The Stakeholders: All of us would benefit from an enhanced understanding of how undergraduates can contribute to diversity and our understanding of inclusivity in the field of HRD. The stakeholders of this article are HRD faculty, undergraduate students, and department and program administrators, as well as anyone who works in an organization that hires or is considering hiring new graduates into HRD positions.